2021
DOI: 10.3390/v13122553
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-Based Detection of Antibodies against SARS-CoV-2 Proteins, Common Respiratory Viruses and Type I Interferons

Abstract: A microarray-based assay to detect IgG and IgM antibodies against betacoronaviruses (SARS-CoV-2, SARS, MERS, OC43, and HKU1), other respiratory viruses and type I interferons (IFN-Is) was developed. This multiplex assay was applied to track antibody cross-reactivity due to previous contact with similar viruses and to identify antibodies against IFN-Is as the markers for severe COVID-19. In total, 278 serum samples from convalescent plasma donors, COVID-19 patients in the intensive care unit (ICU) and patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 48 publications
4
8
1
Order By: Relevance
“…While this broadly contrasts with the findings of others who noted an association between presence of anti-IFN autoantibodies and increased COVID-19 disease severity parameters [2,3,5,7], this difference could be explained by a lack of power in our exploratory study or masking effects of the high standard of care in a high-resource setting. Nevertheless, the proportion of critically ill COVID-19 patients in our cohort with anti-IFN autoantibodies is remarkably consistent with the findings from several independent severe COVID-19 cohorts recently studied across Europe, Asia, and the Americas, despite the use of different detection assays [2][3][4][5][6][7][8][9][10][11]24,25]. Indeed, in the future, it will probably be important to have standardized quantitative assays and reporting standards for such anti-IFN autoantibodies, as varying assay sensitivities may mean that their presence is under or overestimated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While this broadly contrasts with the findings of others who noted an association between presence of anti-IFN autoantibodies and increased COVID-19 disease severity parameters [2,3,5,7], this difference could be explained by a lack of power in our exploratory study or masking effects of the high standard of care in a high-resource setting. Nevertheless, the proportion of critically ill COVID-19 patients in our cohort with anti-IFN autoantibodies is remarkably consistent with the findings from several independent severe COVID-19 cohorts recently studied across Europe, Asia, and the Americas, despite the use of different detection assays [2][3][4][5][6][7][8][9][10][11]24,25]. Indeed, in the future, it will probably be important to have standardized quantitative assays and reporting standards for such anti-IFN autoantibodies, as varying assay sensitivities may mean that their presence is under or overestimated.…”
Section: Discussionsupporting
confidence: 90%
“…We did not identify any patients who were unambiguously positive for anti-IFNβ autoantibodies. The identification of anti-IFN autoantibodies in approximately 10% of severe COVID-19 patients is fully in line with previous reports from others [2][3][4][5][6][7][8][9][10][11].…”
Section: Plos Biologysupporting
confidence: 91%
See 1 more Smart Citation
“…Since most of the collected plasma in our study was from patients with prior history of hospitalization, we evaluated the frequency and the effect of anti-IFN antibodies on clinical outcomes. We found similar frequencies of positivity to those reported in the literature (i.e., ~ 5%) [ 9 , 53 ]. In addition, we found that transfused anti-IFN antibodies did not influence the clinical outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…We have also reported the presence of autoantibodies (auto-Abs) neutralizing high concentrations (10 ng/mL, with plasma diluted 1/10) of IFN-α2 and/or IFN-ω in about 10% of patients with critical COVID-19 pneumonia but not in individuals with asymptomatic or mild infection ( 12 ). This finding has already been replicated in 14 other cohorts ( 20 35 ). We then detected auto-Abs neutralizing lower, more physiological concentrations (100 pg/mL, with plasma diluted 1/10) of IFN-α2 and/or IFN-ω in 13.6% of patients with life-threatening COVID-19, and 18% of deceased patients ( 11 ).…”
mentioning
confidence: 59%